Outcomes Assessment of a Pharmacist-Directed Seamless Care Program in an Ambulatory Oncology Clinic. (February 2014) - Edwards, Scott J.; Abbott, Rick; Edwards, Jonathan; LeBlanc, Michael; Dranitsaris, George; Donnan, Jennifer; Laing, Kara; Whelan, Maria A.; MacKinnon, Neil J.
The primary goal of seamless care is improved patient outcomes and improved standards of care for patients with cancer. The pharmacy service of the Newfoundland Cancer Treatment and Research Foundation conducted a randomized control study that measured clinical and humanistic outcomes of a pharmacist-directed seamless care program in an ambulatory oncology clinic. This article focuses on the intervention group, particularly the identification of drug-related problems (DRPs) and utilization of health care services as well the satisfaction of 3 types of health professionals with the services provided by the pharmacist-directed seamless care program. Overall, the seamless care pharmacist (SCP) identified an average of 3.7 DRPs per intervention patient; the most common DRP reported was a patient not receiving or taking a drug therapy for which there is an indication. The SCP identified more DRPs in patients receiving adjuvant treatment compared to those receiving palliative treatment. On average, family physicians, oncology nurses, and hospital pharmacists were satisfied with the SCP intervention indicating that they agreed the information collected and distributed by the SCP was useful to them. Pharmacist-directed seamless care services in an ambulatory oncology clinic have a significant impact on clinical outcomes and processes of patient care. The presence of a SCP can help identify and resolve DRPs experienced by patients in an outpatient oncology clinic, ensuring that patients are receiving the highest standard of care.